Integrasi Pendidikan Bela Negara dalam Penguatan Ketahanan Pangan Sektor Peternakan sebagai Strategi Pertahanan Nonmiliter - Deriel Kurniawan; Revitia Thalita Salsabila; Gabriel Khoirul Huga (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2026)
Globalization has introduced new challenges to national defense systems through non-military threats such as economic dependencies and food crises. This study analyzes the relationship between livestock food security and national defense education as a non-military defense strategy. Employing a qualitative approach with comparative case study method, this research compares Indonesian cases (North Aceh, South Lampung, Kalimantan, East Nusa Tenggara) with international cases (Tunisia, Algeria, Russia-Ukraine). The units of analysis include Indonesia's livestock food security policies, local livestock empowerment programs such as Desa Tangguh Pangan, TNI initiatives in people's livestock empowerment, and international food security crisis cases. Data were collected through analysis of official government documents, international agency reports (FAO, World Bank, European Commission), and journal articles from 2011-2025. Analysis using the Miles and Huberman model demonstrates that internalization of national defense values contributes to strengthening self-reliance character, solidarity, and collective responsibility in maintaining food security. Findings indicate that the livestock sector can be positioned as non-military defense infrastructure. Comparative results show that Indonesia's approach, which integrates community empowerment with national defense values, demonstrates significant advantages over Tunisia and Algeria's reactive responses with emergency subsidies without domestic capacity building, and differs from Europe's response that remains dependent on global market mechanisms. The study reveals that Indonesia's bottom-up approach transforms communities from passive consumers into active actors with collective responsibility for national food sovereignty. Livestock-based food security represents concrete implementation of national defense in the era of multidimensional threats.